(untitled) (Revista de Estudos da Linguagem, 2025)
This study examines how dynamic modality, specifically the auxiliaries may and can, conveys politeness in nineteenth-century English instructive prose. A typology and the semantics of modality in English have been widely described, with particular emphasis on epistemic and deontic readings (Bybee et al., 1994; Coates, 1983; Hoye, 1997; Nuyts, 2016; Palmer, 2001; van der Auwera & Plungian, 1998). Within politeness research, modals figure centrally among mitigation strategies in requests and directives (Blum-Kulka & Olshtain, 1984; Brown & Levinson, 1987; Leech, 2014). In instructive and household-hygiene genres, especially recipe books and manuals, work in the history of discourse shows how gendered and period-specific conventions condition grammatical and relational choices (Alonso-Almeida, 2013; Taavitsainen & Pahta, 2011). In contrast to the prevailing focus on epistemic and deontic meanings, dynamic modality (e.g., can, may as resources of ability/possibility used to soften directives) remains comparatively underexplored in women’s historical writing, a gap the present study addresses. It uses query-driven concordance searches and normalised frequency profiling, followed by full-context manual reading to disambiguate dynamic, deontic, and epistemic uses in the Corpus of Women’s Instructive Texts in English, 1800–1899 (CoWITE19). It finds that may and can routinely soften directives by framing options and capacities rather than commands; in this corpus, can often presents circumstantial ability and procedural affordances, whereas may licenses alternatives for the reader. It concludes that dynamic modals function as a subtle yet powerful resource that enables women authors to manage authorial persona, maintain politeness, and instruct effectively within nineteenth-century social constraints.